Visuomotor performance at high altitude in COPD patients. Randomized placebo-controlled trial of acetazolamide - Scheiwiller, P. M.; Furian, M.; Buergin, A.; Mayer, L. C.; Schneider, S. R.; Mademilov, M.; Lichtblau, M.; Muralt, L.; Sheraliev, U.; Sooronbaev, T. M.; Ulrich, S.; Bloch, K. E. (Frontiers in Physiology, 2022)
Introduction: We evaluated whether exposure to high altitude impairs visuomotor learning in lowlanders with chronic obstructive pulmonary disease (COPD) and whether this can be prevented by acetazolamide treatment. Methods: 45 patients with COPD, living <800 m, FEV1 ≥40 to <80%predicted, were randomized to acetazolamide (375 mg/d) or placebo, administered 24h before and during a 2-day stay in a clinic at 3100 m. Visuomotor performance was evaluated with a validated, computer-assisted test (Motor-Task-Manager) at 760 m above sea level (baseline, before starting the study drug), within 4h after arrival at 3100 m and in the morning after one night at 3100 m. Main outcome was the directional error (DE) of cursor movements controlled by the participant via mouse on a computer screen during a target tracking task. Effects of high altitude and acetazolamide on DE during an adaptation phase, immediate recall and post-sleep recall were evaluated by regression analyses. www.ClinicalTrials.gov NCT03165890. Results: In 22 patients receiving placebo, DE at 3100 m increased during adaptation by mean 2.5°, 95%CI 2.2° to 2.7° (p < 0.001), during immediate recall by 5.3°, 4.6° to 6.1° (p < 0.001), and post-sleep recall by 5.8°, 5.0 to 6.7° (p < 0.001), vs. corresponding values at 760 m. In 23 participants receiving acetazolamide, corresponding DE were reduced by −0.3° (−0.6° to 0.1°, p = 0.120), −2.7° (−3.7° to −1.6°, p < 0.001) and −3.1° (−4.3° to −2.0°, p < 0.001), compared to placebo at 3100 m. Conclusion: Lowlanders with COPD travelling to 3100 m experienced altitude-induced impairments in immediate and post-sleep recall of a visuomotor task. Preventive acetazolamide treatment mitigated these undesirable effects.